Impact of Educational Intervention Based on Theory of Planned Behavior on Lifestyle Change of Patients with Myocardial Infarction - Tooba Karimy; Mohsen Saffari; Hormoz Sanaeinasab; Kazem Khalagi; Mehdi Hassan-Abadi (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: Cardiovascular disease is the most common cause of death and a major cause of disability in many countries, including Iran. To reduce the effects of heart attacks and their complications, lifestyle and behavioral modification is needed. In this study, the theory of planned behavior was used to find out if an educational intervention could change the lifestyle of patients with myocardial infarction and how much is its effectiveness. Materials and methods: This was a randomized controlled trial conducted on 80 patients with myocardial infarction who live in the city of Bandar Abbas, Iran. The patients were divided into two groups by random allocation- intervention and control group. Those who were in the intervention group participated in 4 educational sessions (at 50 minutes a session, one session per week) in accordance with the theory of planned behavior. A questionnaire consisting of 3 parts was used to gather the data: demographics, Health Promoting Lifestyle Profile (HPLP II), and a researcher-made scale based on constructs from the theory of planned behavior. Content validity was used for validation and the reliability was assessed using Cronbach's alpha test, and the test-re-test. The questionnaire was completed three times through interview: before the intervention, one month and three months after the intervention. Data were analyzed using Chi-square, RMANOVA, and multiple linear regression. Results: The mean age of the participants was 51.5 7 ±7.70 years; 67% were male. One month and three months after the intervention, a significant improvement in the lifestyle of the intervention group compared with the control group was seen (p  0.001>). Also, based on the constructs of the theory (attitudes, subjective norms, perceived behavioral control, behavioral intention and behavior) one month and three months after the intervention, there were considerable increases in the mean scores of the intervention group than the control group (p  0.001>). Conclusions: The educational program designed based on a theoretical foundation is useful to change attitudes, subjective norms, perceived behavioral control and behavioral intention for a healthy lifestyle among patients with myocardial infarction. It also may improve all aspects of lifestyle in such patients. Therefore, assessing the effectiveness of these theory-based educational interventions may be suggested to improve the lifestyle among other patients. Paper Type: Research Article.